Local Wisdom-Based Multicultural Pedagogy: The Foundation of Character and Tolerance Building in Early Childhood Education - Muhammad Akil Musi; Ramlah Yusran; Usman Usman; Nidha Eka Restuti Munawir (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2026)
Early Childhood Education (ECE) plays a pivotal role in shaping children's character and foundational competence. However, integrating local wisdom into the curriculum is often uneven and risks fostering cultural bias if not systematically balanced with broader multicultural values. This study examines the conceptual frameworks, implementation strategies, and effectiveness of local culture integration while developing a comprehensive multicultural teaching model for ECE. Employing a systematic literature review design, this study analyzed peer-reviewed research articles published between 2017 and 2024. The data analysis process advanced through rigorous selection, data display, and conclusion drawing/verification, with trustworthiness established via theoretical triangulation. The synthesis of the literature revealed three core findings: (1) integrating cultural values, folklore, traditional rituals, and cooperative games significantly strengthens children's prosocial behaviors; (2) deploying flexible learning tools spanning digital, print, and physical modalities successfully accommodates diverse early childhood developmental needs; and (3) establishing a curriculum equilibrium fosters an optimal balance between local cultural pride and global tolerance. Grounded in Vygotsky's Socio-cultural Theory and Bronfenbrenner's Bioecological Systems Theory, this study presents a structured pedagogical framework designed to mitigate cultural bias. This is achieved by leveraging educators' cultural competencies, structural policy support, and collaborative community teamwork. Ultimately, this research provides vital theoretical background and practical guidance for curriculum developers and ECE practitioners to engineer culturally sensitive, equitable, and highly inclusive early learning environments.